Comparing the efficacy of mindfulness-based therapy and cognitive-behavioral therapy for depression in head-to-head randomized controlled trials: A systematic review and meta-analysis of equivalence - Sverre, Kristine Trettø; Nissen, Eva Rames; Farver-Vestergaard, Ingeborg; Johannsen, Maja; Zachariae, Robert (Clinical psychology review, 2023)
While Cognitive Behavioral Therapy (CBT) is recommended as first-line treatment for depression, a significant minority do not show an adequate treatment response. Despite evidence for the efficacy of Mindfulness-Based Therapies (MBT) both in treating current depression and preventing relapse, it remains unknown whether MBT and CBT are equivalent in the treatment of current depression. Five databases were searched for randomized controlled trials (RCTs) directly comparing MBT with CBT and including depression as primary or secondary outcome. When pooling the results of 30 independent RCTs with a total of 2750 participants, MBT and CBT were statistically significantly equivalent at both post-intervention (Hedges's g = −0.009; p < .001) and follow-up (g = −0.033; p = .001). Supplementary Bayesian analyses provided further support for the alternative hypothesis of no difference between MBT and CBT. When exploring possible sources of heterogeneity, the differences at follow-up were smaller between CBT and mindfulness-based cognitive therapy (MBCT) than between CBT and mindfulness-based stress-reduction (MBSR) (Slope = 0.37;p = .022). The currently available evidence suggests that that MBT and CBT are equally efficacious in treating current adult depression. It remains unclear whether the similar effects of the two intervention types are due to different mechanisms or common factors. •We tested the equivalence of mindfulness-based therapy (MBT) and cognitive behavioral therapy (CBT) for treating depression.•Thirty randomized controlled trials of a total of 2705 participants were included.•MBT and CBT was statistically significantly equivalent in treating depression at both post-treatment and follow-up.